A novel distance that reduces information loss in continuous characters with few observations - Lo Valvo, Gerardo A. (2023)
Fil: Lo Valvo, Gerardo A. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.